2011
DOI: 10.1007/s10212-011-0062-9
|View full text |Cite
|
Sign up to set email alerts
|

Testing a motivational model of achievement: How students’ mathematical beliefs and interests are related to their achievement

Abstract: Blackwell et al. (Child Development 78(1):246-263, 2007) tested a motivational model of achievement in which an incremental theory of intelligence leads to learning goals and positive effort beliefs, which leads to fewer ability-based, helpless attributions, and more positive strategies, which leads to improved grades. In the present study, we tested this model by using a different population, using domain-specific items, comparing the results across gender, including "interest" as another variable in the mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
64
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(75 citation statements)
references
References 48 publications
(66 reference statements)
6
64
0
5
Order By: Relevance
“…Indeed, study efforts have been found to relate positively to incremental beliefs (Jones, Wilkins, Long, & Wang, 2012) and negatively to entity beliefs (Bodill & Roberts, 2013) whereas procrastination has been associated positively with entity beliefs (Howell & Buro, 2009). …”
Section: Implicit Ability Beliefsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, study efforts have been found to relate positively to incremental beliefs (Jones, Wilkins, Long, & Wang, 2012) and negatively to entity beliefs (Bodill & Roberts, 2013) whereas procrastination has been associated positively with entity beliefs (Howell & Buro, 2009). …”
Section: Implicit Ability Beliefsmentioning
confidence: 99%
“…We expected ability beliefs to predict the study-related correlates, because the more students believe that ability is a fixed entity, the less likely they are to see a reason to invest more effort in studying (Jones et al, 2012) as for these students the locus of control seems to reside to some uncontrollable sources (Bodill & Roberts, 2013). Concomitantly, students with strong entity beliefs may tend to procrastinate their homework more as postponing a should-be-done activity for a later time and substitute it with an enjoying one, may help them cope with the negative emotions arising due to school-related tasks (King, McInerney, & Watkins, 2012) and with an uncomfortable situation where any effort for studying hard is futile (Cury et al, 2008).…”
Section: (Hypothesis 2)mentioning
confidence: 99%
“…Тачније, мотивација за учење математике код ученика средњих школа у већини истраживања није мерена упитницима намење-ним за процену ове врсте мотивације, већ путем појединачних индикатора попут труда у учењу математике (Blackwell et al, 2007), процене корисности самог градива из мате-матике или интересовања за сам предмет (Jones et al, 2012).…”
Section: мотивација за учење математике и имплицитна уверења о интелиunclassified
“…Када се говори о инкременталним теоријама интелигенције и мотивацији за учење математике, у истраживањима се најчешће добија позитивна повезаност ових конструката. У истраживању Џоунса и сарадника (Jones et al, 2012), ученици средњих школа који су поборници инкременталне природе интелигенције показују веће интересовање за учење математике, као и за усавршавањем у овом домену услед уочавања корисности математике за будућу професионалну улогу. Та-кође, инкрементална схватања интелигенције утичу на повећање мотивације за учење математике и редуковање математичке анксиозности код средњошколаца (Burns & Isbell, 2007), а ученици средњих школа који су заговорници инкременталне природе интелектуалних способности уједно улажу више труда у учењу математичког градива (Blackwell et al, 2007).…”
Section: мотивација за учење математике и имплицитна уверења о интелиunclassified
“…Intrinsic value, often associated greatly with enjoyment of doing an activity or task, is quite conceptually similar with interest 4,6 . Interest is a motivational variable that is related to academic achievement 9,10 . Attainment value is the perceived importance and meaningfulness of doing a task; it may also be described as someone's perception of how engaging in a task or domain is consistent with one's identity 4,6 .…”
Section: Literature Reviewmentioning
confidence: 99%